Effects of Atmospheric Composition on the Molecular Structure of Synthesized Silicon Oxycarbides. Issue 10 (20th July 2015) - Narisawa, Masaki; Funabiki, Fuji; Iwase, Akihiro; Wakai, Fumihiro; Hosono, Hideo
Abstract : The dependence of silicon oxycarbides' chemical composition and molecular structure on their reaction conditions was tested by varying the atmosphere under which pyrolysis was performed. To obtain the silicon oxycarbides, densely cross‐linked silicone resin particles with an averaged diameter of 2 μm were pyrolyzed in various atmospheres of H2, Ar, and CO2, in the temperature range 700°C–1100°C. The residual mass of resin after pyrolysis was almost constant at 700°C, although their apparent colors varied distinctly. The sample obtained from the H2 atmosphere was white, whereas that obtained from the CO2 atmosphere was dark brown. Fourier‐transform infrared (FT‐IR) spectra of the residues suggested that the Si–O–Si network evolution was accelerated in the CO2 atmosphere. Beyond 800°C, the chemical compositions of the compounds obtained from a H2 atmosphere increasingly approached near‐stoichiometric SiO2 – x SiC composition with increasing the pyrolysis temperature. Compounds from a CO2 atmosphere approached a composition of SiO2 – x C with no free SiC as the pyrolysis temperature increased. In the products from an Ar atmosphere, SiO2 – x SiC–yC compositions were typically obtained. The observed effects of the pyrolysis atmosphere on the resulting chemical compositions were analyzed in terms of thermodynamic calculations. Electron spin resonance (ESR) spectra revealed broad and intense signals from products obtained from either Ar or CO2 . Estimating from the signal intensity, the residual spin concentrations were in the range 10 18 –10 19 g −1 . Meanwhile, the spectra from the samples obtained in H2 showed weak and sharp signals with estimated spin concentrations ranging from 10 16 –10 17 g −1 . This signal attenuation may have been due to the hydrogen capping of dangling bond formed during pyrolysis.